Measurable residual disease-guided treatment with azacitidine to prevent haematological relapse in patients with myelodysplastic syndrome and acute myeloid leukaemia (RELAZA2): an open-label, multicentre, phase 2 trial. Issue 12 (December 2018) - Platzbecker, Uwe; Middeke, Jan Moritz; Sockel, Katja; Herbst, Regina; Wolf, Dominik; Baldus, Claudia D; Oelschlägel, Uta; Mütherig, Anke; Fransecky, Lars; Noppeney, Richard; Bug, Gesine; Götze, Katharina S; et al.
Summary: Background: Monitoring of measurable residual disease (MRD) in patients with advanced myelodysplastic syndromes (MDS) or acute myeloid leukaemia (AML) who achieve a morphological complete remission can predict haematological relapse. In this prospective study, we aimed to determine whether MRD-guided pre-emptive treatment with azacitidine could prevent relapse in these patients. Methods: The relapse prevention with azacitidine (RELAZA2) study is an open-label, multicentre, phase 2 trial done at nine university health centres in Germany. Patients aged 18 years or older with advanced MDS or AML, who had achieved a complete remission after conventional chemotherapy or allogeneic haemopoietic stem-cell transplantation, were prospectively screened for MRD during 24 months from baseline by either quantitative PCR for mutant NPM1, leukaemia-specific fusion genes ( DEK–NUP 214, RUNX1–RUNX1T1, CBFb–MYH11 ), or analysis of donor-chimaerism in flow cytometry-sorted CD34-positive cells in patients who received allogeneic haemopoietic stem-cell transplantation. MRD-positive patients in confirmed complete remission received azacitidine 75 mg/m 2 per day subcutaneously on days 1–7 of a 29-day cycle for 24 cycles. After six cycles, MRD status was reassessed and patients with major responses (MRD negativity) were eligible for a treatment de-escalation. The primary endpoint was the proportion of patients who were relapse-free and alive 6 months after the start of pre-emptive treatment. Analyses were done per protocol. This trial is registered withClincialTrials.gov, numberNCT01462578, and finished recruitment on Aug 21, 2018. Findings: Between Oct 10, 2011, and Aug 20, 2015, we screened 198 patients with advanced MDS (n=26) or AML (n=172), of whom 60 (30%) developed MRD during the 24-month screening period and 53 (88%) were eligible to start study treatment. 6 months after initiation of azacitidine, 31 (58%, 95% CI 44–72) of 53 patients were relapse-free and alive (p<0·0001; one-sided binomial test for null hypothesis pexp ≤0·3). With a median follow-up of 13 months (IQR 8·5–22·8) after the start of MRD-guided treatment, relapse-free survival at 12 months was 46% (95% CI 32–59) in the 53 patients who were MRD-positive and received azacitidine. In MRD-negative patients, 12-month relapse-free survival was 88% (95% CI 82–94; hazard ratio 6·6 [95% CI 3·7–11·8], p<0·0001). The most common (grade 3–4) adverse event was neutropenia, occurring in 45 (85%) of 53 patients. One patient with neutropenia died because of an infection considered possibly related to study treatment. Interpretation: Pre-emptive therapy with azacitidine can prevent or substantially delay haematological relapse in MRD-positive patients with MDS or AML who are at high risk of relapse. Our study also suggests that continuous MRD negativity during regular MRD monitoring might be prognostic for patient outcomes. Funding: Celgene Pharma, José Carreras Leukaemia Foundation, National Center for Tumor Diseases (NCT), and German Cancer Consortium (DKTK) Foundation.